Distinguish the Cooperative Enterprise Form through Law. Why? How? - Henrÿ, Hagen (Cooperativismo & Desarrollo, 2019)
Against the background of opposite developments in law, which lead to reducing the diversity of enterprise forms, the article presents empirical and legal reasons why this diversity must be maintained through law - instead of other means - for the sake of the legal concept of sustainable development and it suggests a wide notion of democratic participation as that legal feature which distinguishes cooperatives from other forms of enterprise in times when the very notion of enterprise is undergoing radical changes.